Implementation of distance history learning during the Pandemic Covid-19 - Nurjanah, Wulan; Musadad, Akhmad Arif; Purwanta, Hieronymus (Universitas Malikussaleh, 2021)
The Covid-19 pandemic has an impact on all aspects of life including education, hence, the government issued a study from home policy. The Ministry of Education and Culture issued a Circular Letter Number 4 of 2020 concerning the Implementation of the Education Policy for the Emergency Period of the Spread of Covid-19 conveyed that the learning process takes place remotely or learn from home. This policy was issued as an effort to reduce the spread of the virus. This is a challenge and opportunity for the world of education nowadays. Distance learning is carried out online by utilizing technology, information, and communication. The implementation of distance history learning by utilizing technology is very helpful for school on teaching and learning process, but in its progress encountered various obstacles. Facilities and infrastructure that are not adequate, the lack of readiness of teachers and students, as well as the unstable condition of the internet network is a challenge that is often encountered. Therefore, this article seeks to provide an overview of the implementation of distance learning far done during the Covid-19 pandemic. The research was conducted using a descriptive approach qualitative. The object of research was carried out on the history learning process carried out at SMA Negeri 15 Pandeglang which is located at Jalan Raya Carita KM. 05 Labuan, Banjarmasin, Carita, Pandeglang, Banten. Data obtained through primary and secondary sources and researchers as the main instrument. Technique Data collection was done by interview, observation, and document analysis. Researchers use techniques triangulation of sources and methods and analyzed with an interactive model as a data analysis technique. Data obtained through interviews, observation, and document analysis.